The Jeff = 1/2 insulator Sr3Ir2O7 studied by means of angle-resolved photoemission spectroscopy. - Wojek, B; Berntsen, M; Boseggia, S; Boothroyd, A; Prabhakaran, D; McMorrow, D; Rønnow, H; Chang, J; Tjernberg, O (2012)
The low-energy electronic structure of the J(eff) = 1/2 spin-orbit insulator Sr3Ir2O7 has been studied by means of angle-resolved photoemission spectroscopy. A comparison of the results for bilayer Sr3Ir2O7 with available literature data for the related single-layer compound Sr2IrO4 reveals qualitative similarities and similar J(eff) = 1/2 bandwidths for the two materials, but also pronounced differences in the distribution of the spectral weight. In particular, photoemission from J(eff) = 1/2 the states appears to be suppressed. Yet, it is found that the Sr3Ir2O7 data are in overall better agreement with band-structure calculations than the data for Sr2IrO4.